(untitled) (Eurasian Medical Research Periodical, 2022)
This article highlight on the Fungal Coinfections in COVID-19 Patients.. Fungal respiratory infections are a major cause of death in immunocompromised persons and are an increasing global health concern. Concerningly, it has been discovered that some individuals with acute respiratory distress syndrome brought on by corona virus disease19 (COVID-19) are predisposed to airborne fungal co-infections . Common1fungal illnesses found associated with COVID-19 infection1include Aspergillosis, Candidiasis, Cryptococcosis, and Mucormycosis present a synopsis of these symptoms. Aspergillus species, Candida, Cryptococcus neoformans, and fungus of the Mucorales order, respectively, are the causative agents of these infections. Numerous diseases are caused by fungi in both immunocompetent and immunocompromised people.